Biased Nucleotide Composition and Differential Codon Usage Pattern in HIV-1 and HIV-2 - Vidyavijayan, K K; Hassan, Sameer; Precilla, Lucia K; Ashokkumar, Manickam; Chandrasekeran, Padmapriyadharshini; Swaminathan, Soumya; Hanna, Luke Elizabeth (AIDS research and human retroviruses, 2017)
HIV-1 and HIV-2 are closely related retroviruses with differences in pathogenicity and geographic distribution. HIV-2 infection is associated with slower disease progression and transmission, longer latency period, low or undetectable plasmatic viral loads, and reduced likelihood of progression to AIDS, compared to HIV-1. In this investigation, we analyzed HIV-2 genes and genomes and compared them with that of HIV-1 belonging to various subtypes. Comparative analysis of the effective number of codons (ENC) for each of the nine genes of the two viruses revealed that the tat gene of HIV-2 had a higher ENC value compared to HIV-1 tat, reflecting lower levels of expression of HIV-2 tat. Lower levels of tat protein particularly during the early stages of infection could result in a lower viral load, lower viral set point, and delayed progression of disease in HIV-2-infected individuals compared to HIV-1-infected subjects. Furthermore, the GC3 composition of the regulatory genes of HIV-2 was ≥50%, suggesting a firm effort by these viruses to adapt themselves to evolutionary survival. We hypothesize that differential codon usage could be one of the possible factors that could contribute to the diminished pathogenicity of HIV-2 in the host as compared to HIV-1.